Changes in Sphingolipid Profile of Benzo[a]pyrene-Transformed Human Bronchial Epithelial Cells Are Reflected in the Altered Composition of Sphingolipids in Their Exosomes - Machala, Miroslav; Slavík, Josef; Kováč, Ondrej; Procházková, Jiřina; Pěnčíková, Kateřina; Pařenicová, Martina; Straková, Nicol; Kotouček, Jan; Kulich, Pavel; Mollerup, Steen; Vondráček, Jan; Hýžďalová, Martina (International journal of molecular sciences, 2021)
Sphingolipids (SLs), glycosphingolipids (GSLs), and eicosanoids are bioactive lipids, which play important roles in the etiology of various diseases, including cancer. However, their content and roles in cancer cells, and in particular in the exosomes derived from tumor cells, remain insufficiently characterized. In this study, we evaluated alterations of SL and GSL levels in transformed cells and their exosomes, using comparative HPLC-MS/MS analysis of parental human bronchial epithelial cells HBEC-12KT and their derivative, benzo[a]pyrene-transformed HBEC-12KT-B1 cells with the acquired mesenchymal phenotype. We examined in parallel SL/GSL contents in the exosomes released from both cell lines. We found significant alterations of the SL/GSL profile in the transformed cell line, which corresponded well with alterations of the SL/GSL profile in exosomes derived from these cells. This suggested that a majority of SLs and GSLs were transported by exosomes in the same relative pattern as in the cells of origin. The only exceptions included decreased contents of sphingosin, sphingosin-1-phosphate, and lactosylceramide in exosomes derived from the transformed cells, as compared with the exosomes derived from the parental cell line. Importantly, we found increased levels of ceramide phosphate, globoside Gb3, and ganglioside GD3 in the exosomes derived from the transformed cells. These positive modulators of epithelial-mesenchymal transition and other pro-carcinogenic processes might thus also contribute to cancer progression in recipient cells. In addition, the transformed HBEC-12KT-B1 cells also produced increased amounts of eicosanoids, in particular prostaglandin E2. Taken together, the exosomes derived from the transformed cells with specifically upregulated SL and GSL species, and increased levels of eicosanoids, might contribute to changes within the cancer microenvironment and in recipient cells, which could in turn participate in cancer development. Future studies should address specific roles of individual SL and GSL species identified in the present study.
Keywords: Bronchi; Respiratory Mucosa; buněčné linie; Carcinogens; Cell Transformation, Neoplastic; nádorová transformace buněk; Humans; sphingolipid; Cell Line; eicosanoids; Exosomes; Sphingolipids; karcinogeny; exozómy; benzopyren; in vitro cell transformation; glycosphingolipid; Benzo(a)pyrene; exosomes; respirační sliznice; lidé; bronchy; sfingolipidy